Implementation of Low Impact Development for Reducing Surface Runoff: A Case Study of Bumi Harapan Residential Area, Cileunyi - Naya Dhia Ulhaq; Rakhmat Yusuf (Politeknik Negeri Lhokseumawe, 2025)
This study analyzes surface runoff and evaluates the effectiveness of Low Impact Development (LID) in the Bumi Harapan residential area, Cileunyi District, Bandung Regency. A descriptive quantitative method was applied using hydrological modeling with PCSWMM. Rainfall data from Cibiru and Cileunyi stations were analyzed, and the log normal distribution with a 2-year return period (83.22 mm) was selected. Rainfall intensity was modeled using the SCS Type I method with a 15-minute interval. The drainage model consisted of 26 subcatchments, 108 junctions, 133 conduits, 1 pump, and 2 outfalls. Initial results showed an average runoff of 79.92 mm, ranging from 65.89 mm (S24) to 81.63 mm (S18). After applying LID controls (rain barrels, rain gardens, bioretention, and permeable pavements), runoff volume decreased significantlyâ€”up to 64%, with reductions from 61.61 mm (S26) to 4.29 mm (S24). These results highlight LIDâ€™s potential for sustainable stormwater management.Â